2000
DOI: 10.1073/pnas.97.17.9591
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of hemoglobin A synthesis in erythroid cells from peripheral blood of thalassemic patients

Abstract: Mononuclear cells from peripheral blood of thalassemic patients were treated with morpholino oligonucleotides antisense to aberrant splice sites in mutant ␤-globin precursor mRNAs (premRNAs). The oligonucleotides restored correct splicing and translation of ␤-globin mRNA, increasing the hemoglobin (Hb) A synthesis in erythroid cells from patients with IVS2-654͞␤ E , IVS2-745͞ IVS2-745, and IVS2-745͞IVS2-1 genotypes. The maximal Hb A level for repaired IVS2-745 mutation was Ϸ30% of normal; Hb A was still detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
111
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(113 citation statements)
references
References 33 publications
1
111
0
1
Order By: Relevance
“…25 One such modification in oligomer chemistry has led to the development of the phosphorodiamidate morpholino oligomers (PMO) by AVI BioPharma Inc. (Portland, OR), which are non-ionic antisense agents that inhibit gene expression by binding to RNA and sterically blocking processing or translation in an RNaseH-independent manner. [26][27][28] PMO antisense agents have revealed excellent safety profile and efficacy in multiple disease models [29][30][31][32][33][34][35][36][37] including cancer preclinical studies. [38][39][40][41][42][43][44] Recent studies in our laboratory have characterized in vivo PMO bioavailability in solid tumors and pharmacokinetics of the PMO agents in human clinical trials, revealing the potential of these agents in gene-specific targeting.…”
Section: Genomic-based Strategiesmentioning
confidence: 99%
“…25 One such modification in oligomer chemistry has led to the development of the phosphorodiamidate morpholino oligomers (PMO) by AVI BioPharma Inc. (Portland, OR), which are non-ionic antisense agents that inhibit gene expression by binding to RNA and sterically blocking processing or translation in an RNaseH-independent manner. [26][27][28] PMO antisense agents have revealed excellent safety profile and efficacy in multiple disease models [29][30][31][32][33][34][35][36][37] including cancer preclinical studies. [38][39][40][41][42][43][44] Recent studies in our laboratory have characterized in vivo PMO bioavailability in solid tumors and pharmacokinetics of the PMO agents in human clinical trials, revealing the potential of these agents in gene-specific targeting.…”
Section: Genomic-based Strategiesmentioning
confidence: 99%
“…Work in this laboratory showed that splice-switching oligonucleotides (SSOs), which block aberrant splice sites in IVS2-654 and other pre-mRNAs (IVS1-5, IVS1-6, IVS1-110, IVS2-705, and IVS2-745) as well as in the coding sequence (HbE) of the ␤-globin gene, force the splicing machinery to reselect the existing correct splice sites, repairing the splicing pattern of ␤-globin pre-mRNA. This repair, which restores production of correctly spliced ␤-globin mRNA and protein, was accomplished in several in vitro systems and ex vivo in erythroid progenitor cells from thalassemic patients (6)(7)(8)(9)(10)(11)(12). In this study, we investigated the effectiveness in thalassemic splicing correction of a modified morpholino oligomer, SSO 654-P005, in a mouse model of IVS2-654 ␤-thalassemia.…”
mentioning
confidence: 99%
“…Antisense oligonucleotides have been used to restore pre-mRNA splicing in other disease models (1)(2)(3)(4)(5)(6)(7)(8); however, the therapeutic rationale for each varies considerably and, to our knowledge, none has addressed an intranuclear or DNA repair disorder. Furthermore, we believe that A-T offers several advantages for exploring the therapeutic potential of AMOs, such as (i) the availability of many surrogate markers for evaluating ATM function, ex vivo and in vivo, and (ii) a well characterized spectrum of ATM mutations supported by an extensive cell repository of lymphoblastoid cell lines (LCLs) derived from patients with those mutations (9)(10)(11)(12).…”
mentioning
confidence: 99%